Phosphatidylcholine-specific phospholipase C inhibition down- regulates CXCR4 expression and interferes with proliferation, invasion and glycolysis in glioma cells - Mercurio, Laura (PLoS One, 2017)
BACKGROUND: The chemokine receptor CXCR4 plays a crucial role in tumors, including glioblastoma multiforme (GBM), the most aggressive glioma. Phosphatidylcholine-specific phospholipase C (PC-PLC), a catabolic enzyme of PC metabolism, is involved in several aspects of cancer biology and its inhibition down-modulates the expression of growth factor membrane receptors interfering with their signaling pathways. In the present work we investigated the possible interplay between CXCR4 and PC-PLC in GBM cells. METHODS: Confocal microscopy, immunoprecipitation, western blot analyses, and the evaluation of migration and invasion potential were performed on U87MG cells after PC-PLC inhibition with the xanthate D609. The intracellular metabolome was investigated by magnetic resonance spectroscopy; lactate levels and lactate dehydrogenase (LDH) activity were analyzed by colorimetric assay. RESULTS: Our studies demonstrated that CXCR4 and PC-PLC co-localize and are associated on U87MG cell membrane. D609 reduced CXCR4 expression, cell proliferation and invasion, interfering with AKT and EGFR activation and expression. Metabolic analyses showed a decrease in intracellular lactate concentration together with a decrement in LDH activity. CONCLUSIONS: Our data suggest that inhibition of PC-PLC could represent a new molecular approach in glioma biology not only for its ability in modulating cell metabolism, glioma growth and motility, but also for its inhibitory effect on crucial molecules involved in cancer progression.